Influential Factors on Maternal Self-Efficacy in Exclusive Breastfeeding Among Tengger Tribe Toddlers - Muniroh, Lailatul; Sulistyorini, Yuly; Abihail, Chrysoprase Thasya (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2024)
Exclusive breastfeeding is the action in which the infant only receives breast milk without any additional food or drink including water. In 2022, coverage of exclusive breastfeeding in Indonesia and East Java respectively is 72.04%. However, the coverage of exclusive breastfeeding in the Tengger Tribe is still low, only 38%. This study aims to determine what factors that influenced exclusive breastfeeding self-efficacy practices in toddlers in the Tengger Tribe. This research is an analytic observational study with a cross-sectional study design targeting mothers with children aged 6-24 months in Wonokitri Village, Tosari District, Pasuruan Regency. The research was conducted in April-August 2022. Data analysis used univariate and bivariate analysis using the chi-square test. Most of the respondents were aged 20-34 years (78.9%), mothers had a good level of knowledge (70.2%), fathers and mothers had low levels of education (71.9%), worked as farmers (86%; 61.4%), income UMK (78.9%), children aged 13-24 months (68.4%), male (56.1%), 1st child (38.6%), no cultural influences during childbirth, breastfeeding, and toddlers (93%, 56.1%, 52.6%) and good family support (68.4%). Most mothers have sufficient self-efficacy (52.6%). From the bivariate results, there was no relationship between internal and external factors and the mother’s self-efficacy in exclusive breastfeeding except for the order of the children (p = 0.004). Order of children was the factor associated with the mother’s self-efficacy in exclusive breastfeeding to toddlers in the Tengger Tribe. However, it’s vital to carry out a more in-depth investigation of the internal and external factors that have already been researched in this study.